Análise das estratégias de sustentabilidade ambiental no Tribunal de Justiça do Estado de Goiás (TJGO) - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
In the search for capitalism's development in the last centuries, phenomena such as environmental degradation, the economic globalization and consumption patterns, aggravated inequality and the environmental crisis. Then, the need to rethink and redefine human actions showed itself, otherwise an environment needed for survival in the future wouldn't exist. International actions and environmental concerns culminated in concrete actions that, in turn, provided an opportunity for a broad debate and the institutionalization of environmentally sustainable practices in the private sector and also in public administration. In this sense, we sought to understand the process of institutionalization of environmental management within the Judiciary, notably in the courts in the Midwest region and focusing on the Court of Justice of the State of Goiás, through the study of its environmental public policies, materialized, for the most part, by the Sustainable Logistics Plan. In order to achieve results, bibliographic research was carried out, as well as documentary research on legislation and an exploratory study in the context of the courts of justice in the Midwest, focusing on the TJGO. The results obtained point to a relative advance of environmental sustainability within the scope of these courts through the guidelines established by the National Council of Justice regarding the establishment of permanent socioenvironmental units, the creation of Sustainable Logistics Plans with initiatives to save energy, water, telephone, correct disposal of solid waste, environmental awareness, among others, especially in the search for compatibility with the United Nations' Sustainable Development Goals. However, there is much to improve in terms of effectiveness of these environmental policies. In order for all the goals of the TJGO Sustainable Logistics Plan and the entire Judiciary to be met continuously, in addition to an effective promotion of sustainability, it is necessary to engage all members, servers and collaborators in this challenge.
Analysis of environmental sustainability strategies in the Court of Justice of the State of Goiás (TJGO)
Keywords: Gestão ambiental; Poder Judiciário; Legislação; Environmental management; Judicial Power; Legislation; SANEAMENTO AMBIENTAL::LEGISLACAO AMBIENTAL; SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL; ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA